Uso de ferramentas computacionais para análise de modificações na ambiência urbana de sítio histórico tombado : ensaio em Santa Leopoldina-ES - Queiroz, Rodrigo Zotelli (2013)
In order to propose, in a straight and uniform way, a model to analyze changes in the urban ambience in Santa Leopoldina Historic Heritage Site, this research starts with a bibliographical research aiming to understand - specially through the reading of t